[Zinc(II)(Pyridine‐Containing Ligand)] Complexes as Single‐Component Efficient Catalyst for Chemical Fixation of CO2 with Epoxides. Issue 19 (18th May 2021) - Cavalleri, Matteo; Panza, Nicola; di Biase, Armando; Tseberlidis, Giorgio; Rizzato, Silvia; Abbiati, Giorgio; Caselli, Alessandro
Abstract: The reaction between epoxides and CO2 to yield cyclic carbonates is efficiently promoted under solvent‐free and relatively mild reaction conditions (0.5 mol % catalyst loading, 0.8 MPa, 125 °C) by zinc(II) complexes of pyridine containing macrocyclic ligands (Pc−L pyridinophanes). The zinc complexes have been fully characterized, including X‐ray structural determination. The [Zn(II)X(Pc−L)]X complexes showed good solubility in several polar solvents, including cyclic carbonates. The scope of the reaction under solvent‐free conditions has been studied and good to quantitative conversions with excellent selectivities have been obtained, starting from terminal epoxides. When solvent‐free conditions were not possible (solid epoxides or low solubility of the catalyst in the oxirane) the use of cyclic carbonates as solvents has been successfully investigated. The remarkable stability of the catalytic system has been demonstrated by a series of consecutive runs. Abstract : Pentacoordinated [Zn II (X)(Pc−L)]X (with X=Cl, Br, I) complexes, which can be easily prepared in high yields starting from cheap and available reagents, are efficient bifunctional catalyst for the cycloaddition of CO2 to epoxide under solvent‐free and relatively mild reaction condition (0.8 MPa in 3 h at 125 °C, with a 0.5 mol % of cat.). The reusability of the metal complex has been assessed by restoring the catalytic cycle for four consecutive runs.